THE REVOLUTION OF ARABIC LANGUAGE LEARNING MEDIA: CHALLENGES AND SOLUTIONS IN 3T AREAS (REMOTE, FRONTIER, OUTERMOST) - Muhammad Rasyid Ridha (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
Education plays a crucial role in a nation's development and civilization. However, regions categorized as underdeveloped, frontier, and outermost (3T) in Indonesia face significant challenges in providing quality education, including Arabic language learning. Arabic, as the language of the Qur'an and a key reference in Islamic teachings, is essential for students seeking a deeper understanding of religious texts. Nevertheless, Arabic learning in 3T areas is hindered by linguistic and non-linguistic factors, such as difficulties in grammar and pronunciation, low student motivation, inadequate learning facilities, and ineffective teaching methods. This study employs a literature review method, analyzing various academic sources to explore the challenges and potential solutions for Arabic language learning in 3T regions. The research highlights that the use of innovative educational media significantly enhances students' motivation and comprehension. However, implementing digitalbased learning tools remains a challenge due to limited internet access, lack of technological infrastructure, and insufficient teacher training. To address these challenges, this study proposes several solutions, including improving infrastructure, integrating local cultural resources into the curriculum, and providing teacher training programs on innovative teaching methods. Game-based learning, such as Arabic Monopoly, flashcards, and interactive storytelling, has proven effective in increasing student engagement. Additionally, traditional games like spinning tops (gasing) and congklak, adapted to Arabic language learning, can serve as culturally relevant teaching tools. The findings emphasize the need for collaborative efforts among educators, policymakers, and institutions to support Arabic language education in 3T areas. By combining digital innovations with traditional learning strategies, a more inclusive and effective learning environment can be established. This research contributes to developing sustainable and context-appropriate Arabic language learning strategies, ensuring equitable education opportunities in remote regions.